Fibre/polyethylene reinforced composites: a review - Aji, Isuwa Suleiman; Salit, Mohd Sapuan; Zainudin, Edi Syams; Abdan, Khalina (2009)
Two of the most commonly produced polyolefin are polyethylene (PE) and Polypropylene (PP), which is widely used in a variety of industrial application such as films, bags and fibres. In addition, PE is used as an extrusion aid and releases agent in some polymer systems as well as additive in hot-melt additives and possesses good mechanical properties, easy processability, low cost and recyclability, in addition, it has the possibility of decreasing brittleness of composite. Adequate mixing of PE with natural fibre can produce composite of optimum quality which can be use in various engineering applications especially in the use of maleated polyethylene (MAPE) and fibre treatment with alkaline, then silanes in that order. While alkaline treatments helps to increases the surface roughness of fibres therefore resulting in better mechanical adhesion, increase the amount of cellulose exposed on the fibre surface, thus increasing the number of possible reaction sites, and thirdly, remove lignin and other alkaline soluble compounds from fibre thereby increasing the number of reactive sites on the fibre surface, silanization results in better interfacial load transfer efficiency. Challenges in this growing area of research is the issue of wettability during fibre loading which if inadequate, can cause fibre pullout during operation since a polar and non-polar material is compounded to produce the composites. Depending on the fibre type, there is an optimal fibre content and length for which fibre-reinforced composites show the best properties.